Avatars des Centaures : du mythe à la fantasy - Hélène Gallé (Strenae)
The figure of the centaur, which has been constantly revised over the centuries, has become more widespread in recent times, in children’s literature and more generally in fantasy, which reaches a wider audience. Is there permanence or evolution in the mythical figure of the centaur? How does the centaur fit into this new magical landscape developing in contemporary literature?